Development and test of a real-size MRPC for CBM-TOF - Wang, Y.; Lyu, P.; Huang, X.; Han, D.; Xie, B.; Li, Y.; Herrmann, Norbert; Deppner, Ingo Martin; Simon, Christian; Loizeau, Pierre-Alain; Weidenkaff, Philipp; Frühauf, J.; et al. (Journal of Instrumentation, 2016)
In the CBM (Compressed Baryonic Matter) experiment constructed at the Facility for Anti-proton and Ion Research (Fair) at GSI, Darmstadt, Germany, MRPC(Multi-gap Resistive Plate Chamber) is adopted to construct the large TOF (Time-of-Flight) system to achieve an unprecedented precision of hadron identification, benefiting from its good time resolution, relatively high efficiency and low construction price. Aiming at CBM TOF, we've developed a kind of double-ended readout strip MRPC which applies low resistive glass to keep good performance of time resolution under high-rate condition. There are 24 strips on one counter, and each is carefully designed to match the 100 Ω impedance of PADI electronics. The prototype of this strip MRPC has been tested with cosmic ray, a 98% efficiency and 60ps time resolution is gotten. In order to further examine the performance of the detector working under higher particle flux rate, the prototype has been tested in the 2014 October GSI beam time and 2015 February CERN beam time. In both beam times a relatively high rate of 1 kHz/cm2 was obtained. The calibration is done with CBM ROOT, and an efficiency of 97% and time resolution of 48ps are obtained. All these results show that the real-size prototype is fully capable of the requirement of the CBM-TOF, and new designs such as self-sealed are modified into the strip counter prototype to obtain even better performance.